To study the effectiveness of umbilical cord blood transfusion in neonates at tertiary health care centre - Shoaib Beg Mirza; Deepak Dwivedi; Shabd Singh Yadav; Naresh Bajaj (Advances in Human Biology, 2022)
Introduction: Blood transfusions (BTs) are often required by neonates for different indications. There is usually a deficiency of available blood because of the non-availability of donors, lack of awareness, irrational demand, poor supply chain management system, etc., especially in developing countries. This study was done to determine the usefulness of umbilical cord blood (UCB) as an alternative to adult blood (AB) in neonates and to compare the change in haematological parameters after transfusion and compare outcomes. Materials and Methods: It was a prospective interventional study of UCB transfusions given to neonates requiring blood. UCB was collected in the labour room, under all aseptic precautions, and pretesting was done in the blood bank. Neonates fulfilling inclusion criteria were included. UCB and AB were given as per availability and consent. Post blood analysis was done after 6 h of transfusion watched for reactions. Outcomes such as death, discharge and duration of hospital stay were analysed. Results: A total of 91 BTs were performed, out of which 34 received UCB and 57 with AB. The mean rise of haemoglobin in UCB transfused patients was 2.01 g/dl. Conclusions: In neonates requiring BT, whole UCB is a good and safe alternative to whole AB.